NOVEL TECHNIQUES FOR REDUCING COOLING TIME IN POLYMER INJECTION MOULDS USING RAPID TOOLING TECHNOLOGIES - ALTAF, KHURRAM (2012)
In this research, thermal simulations and injection moulding experiments were performed to compare moulds having cooling channels of circular cross section and those with profiled cross section channels. Studies have been performed on the cooling time reduction in plastic injection moulding by different techniques utilizing thermal simulations and thermal measurements during experiments. Rapid Tooling (RT) technique, which is a manufacturing technique used to produce injection mould tools in a short period of time, has been applied in this research to fabricate injection moulds having circular and profiled conformal cooling channels. Injection moulding experiments for parts was done with these RT moulds using a vertical injection moulding machine. Manufacturing of mould patterns was done using 3-dimensional Printer Rapid Prototyping machine which used wax as the build material. Wax patterns were designed, fabricated and used to fabricate the mould cavity and channels. Aluminum Filled Epoxy material was used for the fabrication of mould cavities having circular conformal cooling channels and profiled conformal cooling channels. As the thermal conductivity of aluminum filled epoxy is much lower than metal moulds, another innovative concept which was embedding a metal insert around the cavity, was also applied for enhancing the heat dissipation. The metal insert was fabricated from aluminum. The concept was tested by fabricating moulds with aluminum inserts. All moulds were tested by injection moulding experiments with embedded thermocouples to measure the temperature of the cavity surface and temperatures were recorded with a data logger. Analysis of the temperature data indicated that the profiled channels had an increased heat dissipation and reduction of cooling time of about 17 percent over the circular channels. With the moulds having aluminum inserts, there was an impressive increase in cooling rate and the cooling time was further reduced by over 50 percent as compared to moulds without inserts.